Education through ICT Initiatives during the Pandemic in India - Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
The global crisis of the COVID-19 virus has impacted the Education Sector tremendously. It has presented the education community around the globe with numerous challenges in continuing the learning process. The Indian Education system has also experienced an irreversible learning crisis amid the pandemic. School closure across the country has impacted everyone's learning experience. The pandemic has forced the sector to shift to a virtual and blended mode of learning. Information and Communication Technology (ICT) has helped the sector to survive and adapt to the new ways of online learning. The crisis has allowed various educational innovations to bloom. Stakeholders across the country have been trying their best to come together and innovate with various ways to support the students and teachers. Considering the various challenges of digital education in the country, efforts have been made by the country to optimize the potential of the existing and new educational platforms to be made available for everyone. During the pandemic, the country has witnessed a number of ICT driven initiatives on national, state, and individual levels. There has been a proactive approach in the education sector to utilize the maximum potential of technology to reach every learner. This paper examines a few such initiatives which have contributed significantly to making it possible for education to reach the remotest corners of the country with the help of technology-related tools.
Keywords: 330